Rhizobium Inoculant and Seed-Applied Fungicide Effects Improve the Drought Tolerance of Soybean Plants as an Effective Agroecological Solution under Climate Change Conditions - Tetiana Nyzhnyk; Sergii Kots; Petro Pukhtaievych (Frontiers in Bioscience-Elite, 2024)
Background: Rhizobial inoculation in combination with fungicidal seed treatment is an effective solution for improving soybean resistance to modern climate changes due to the maximum implementation of the plant’s stress-protective antioxidant properties and their nitrogen-fixing potential, which will contribute to the preservation of the environment. Methods: Model ecosystems at different stages of legume–rhizobial symbiosis formation, created by treatment before sowing soybean seeds with a fungicide (fludioxonil, 25 g/L) and inoculation with an active strain of Bradyrhizobium japonicum (titer 109 cells per mL), were subjected to microbiological, biochemical, and physiological testing methods in controlled and field conditions. Results: Seed treatment with fungicide and rhizobia showed different patterns in the dynamics of key antioxidant enzymes in soybean nodules under drought conditions. Superoxide dismutase activity increased by 32.7% under moderate stress, while catalase increased by 90.6% under long-term stress. An increase in the antioxidant enzyme activity induced the regulation of lipoperoxidation processes during drought and after the restoration of irrigation. Regeneration after stress was evident in soybean plants with a combination of fungicide seed treatment and rhizobial inoculant, where enzyme levels and lipoperoxidation processes returned to control plant levels. Applying seed treatment with fungicide and Rhizobium led to the preservation of the symbiotic apparatus functioning in drought conditions. As proof of this, molecular nitrogen fixation by nodules has a higher efficiency of 25.6% compared to soybeans without fungicide treatment. In the field, fungicidal treatment of seeds in a complex with rhizobia inoculant induced prolongation of the symbiotic apparatus functioning in the reproductive period of soybean ontogenesis. This positively affected the nitrogen-fixing activity of soybeans during the pod formation stage by more than 71.7%, as well as increasing soybean yield by 12.7% in the field. Conclusions: The application of Rhizobium inoculant and fungicide to seeds contributed to the development of antioxidant protection of soybean plants during droughts due to the activation of key enzymatic complexes and regulation of lipoperoxidation processes, which have a positive effect on nitrogen fixation and productivity of soybeans. This is a necessary element in soybean agrotechnologies to improve plant adaptation and resilience in the context of modern climate change.